2005
DOI: 10.1101/gad.1311805
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and oxidative stress resistance in Drosophila are mediated through the eIF4E-binding protein, d4E-BP

Abstract: eIF4E, the mRNA 5 cap-binding protein, is regulated by its binding protein (4E-BP), a downstream target of phosphatidylinositol-3-OH kinase [PI(3)K] signaling. We show thatDrosophila 4E-BP (d4E-BP) activity becomes critical for survival under dietary restriction and oxidative stress, and is linked to life span. The Drosophila forkhead transcription factor (dFOXO) activates d4E-BP transcription. We show that ectopic expression of d4E-BP in dFOXO-null flies restores oxidative stress resistance to control levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 28 publications
7
159
1
2
Order By: Relevance
“…It was expected that transcript levels of both insulin receptor and 4EBP would increase due to starvation as is seen in flies (Tettweiler et al, 2005;Puig and Tjian, 2006). Figure 10A reveals that there was only a slight increase in insulin receptor transcript between larvae that have been starved for 30 hours and their age-matched fed counterparts (V2) (one-way ANOVA, F=1.757, p=0.2063).…”
Section: A B Changes In Insulin Receptor Transcript Due To Starvationmentioning
confidence: 87%
See 2 more Smart Citations
“…It was expected that transcript levels of both insulin receptor and 4EBP would increase due to starvation as is seen in flies (Tettweiler et al, 2005;Puig and Tjian, 2006). Figure 10A reveals that there was only a slight increase in insulin receptor transcript between larvae that have been starved for 30 hours and their age-matched fed counterparts (V2) (one-way ANOVA, F=1.757, p=0.2063).…”
Section: A B Changes In Insulin Receptor Transcript Due To Starvationmentioning
confidence: 87%
“…Insulin receptor transcript levels have been shown to increase in response to starvation (Chen et al, 1996;Tettweiler et al, 2005;Puig and Tjian, 2006). 4EBP is a negative regulator of growth and as such has been shown to be concomitantly upregulated in response to starvation (Tettweiler et al, 2005;Puig and Tjian, 2006).…”
Section: Chapter Twomentioning
confidence: 99%
See 1 more Smart Citation
“…In flies, fasting-dependent protection against oxidative stress is mediated by d4E-BP, which acts downstream of the PI3K/Akt/dFOXO3 pathway (Tettweiler et al, 2005). d4E-BP binds to eIF4E and represses translation.…”
Section: Starvation and Stress Resistancementioning
confidence: 99%
“…Studies in yeast and higher eukaryotes have shown that lowered TOR (and/or decreased IIS in higher eukaryotes) signaling pathway activity increases lifespan (Kenyon et al, 1993;Guarente and Kenyon, 2000;Vellai et al, 2003;Hwangbo et al, 2004;Kapahi et al, 2004;Kaeberlein et al, 2005;Powers et al, 2006). In addition, decreased IIS/TOR signaling activity is associated with increased resistance to some types of stress, suggesting that this pathway plays also an important role in the adaption to different stress conditions (Scott et al, 2002;Holzenberger et al, 2003;Broughton et al, 2005;Teleman et al, 2005;Tettweiler et al, 2005;Powers et al, 2006). In the following section, we will review extra-and intracellular cues that modulate TOR signaling.…”
Section: Stress and Mtormentioning
confidence: 99%